Estudo de método de extração de máxima potência de aerogeradores de baixa potência com modulação em frequência - Casagrande, Matheus Variani (2021)
The use of wind energy to generate electricity has increased over the years. In order to contribute to the study of this renewable energy source, this course conclusion work aims to simulate a maximum power extraction method applied to the topology of an AC-DC converter that will convert the energy of a 2 kW wind generator. As a result of the comparison between different generators, converter topologies and maximum power extraction methods, the permanent magnet synchronous generator, the single switching isolated rectifier double bridge converter and the TSR method were chosen to maintain the maximum power point of the system.